2017
DOI: 10.14419/ijet.v7i1.1.10796
|View full text |Cite
|
Sign up to set email alerts
|

A study on die sinking EDM of Nimonic C-263 super alloy : an intelligent approach to predict the process parameters using ANN

Abstract: In current study, machining characteristics of Nimonic C-263 are analysed by TAGUCHI and modelled using Artificial Neural Networks (ANN). The response parameters under consideration are Material Erosion Rate (MER), Electrode Wear Rate (EWR), Surface Roughness (SR) and Dimensional Overcut (DOC). A regression mathematical model is also developed to verify the capabilities of ANN. The modelling of ANN includes identifying appropriate combination of hidden layers and number of neurons in each hidden layer. Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Chekuri et al [102] predicted the process parameters of EDM of Nimonic C263 with the Cu-electrode by employing regression and ANN models. The analysis showed that IP was the most significant input parameter affecting the output parameters, viz., electrode wear rate, material erosion rate, SR, and dimensional overcut, followed by T on and T off .…”
Section: Literatures On Edm Of Nimonic Alloymentioning
confidence: 99%
“…Chekuri et al [102] predicted the process parameters of EDM of Nimonic C263 with the Cu-electrode by employing regression and ANN models. The analysis showed that IP was the most significant input parameter affecting the output parameters, viz., electrode wear rate, material erosion rate, SR, and dimensional overcut, followed by T on and T off .…”
Section: Literatures On Edm Of Nimonic Alloymentioning
confidence: 99%